ACCOUNTING OF OPERATIONS BETWEEN A COMMERCIAL BANK AND AN ENTERPRISE AND THEIR LEGAL AND REGULATORY FRAMEWORK - Abdukhalimova , Marjona Khikmatovna (THE INNOVATION ECONOMY, 2026)
This scientific article examines the accounting treatment of operations between banks and enterprises and their legal and regulatory framework. The study analyzes settlement, credit, and deposit transactions conducted through bank accounts based on International Financial Reporting Standards and national regulatory documents. The findings indicate that proper compliance with legal and regulatory requirements in accounting for banking operations ensures the reliability and transparency of financial statements. The results of the study have both scientific and practical significance for improving accounting practices.